Evolution of an Amniote-Specific Mechanism for Modulating Ubiquitin Signaling via Phosphoregulation of the E2 Enzyme UBE2D3. (12th March 2020) - Roman-Trufero, Monica; Ito, Constance M; Pedebos, Conrado; Magdalou, Indiana; Wang, Yi-Fang; Karimi, Mohammad M; Moyon, Benjamin; Webster, Zoe; di Gregorio, Aida; Azuara, Veronique; Khalid, Syma; Speck, Christian; et al.
Abstract: Genetic variation in the enzymes that catalyze posttranslational modification of proteins is a potentially important source of phenotypic variation during evolution. Ubiquitination is one such modification that affects turnover of virtually all of the proteins in the cell in addition to roles in signaling and epigenetic regulation. UBE2D3 is a promiscuous E2 enzyme, which acts as an ubiquitin donor for E3 ligases that catalyze ubiquitination of developmentally important proteins. We have used protein sequence comparison of UBE2D3 orthologs to identify a position in the C-terminal α-helical region of UBE2D3 that is occupied by a conserved serine in amniotes and by alanine in anamniote vertebrate and invertebrate lineages. Acquisition of the serine (S138) in the common ancestor to modern amniotes created a phosphorylation site for Aurora B. Phosphorylation of S138 disrupts the structure of UBE2D3 and reduces the level of the protein in mouse embryonic stem cells (ESCs). Substitution of S138 with the anamniote alanine (S138A) increases the level of UBE2D3 in ESCs as well as being a gain of function early embryonic lethal mutation in mice. When mutant S138A ESCs were differentiated into extraembryonic primitive endoderm, levels of the PDGFRα and FGFR1 receptor tyrosine kinases were reduced and primitive endoderm differentiation was compromised. Proximity ligation analysis showed increased interaction between UBE2D3 and the E3 ligase CBL and between CBL and the receptor tyrosine kinases. Our results identify a sequence change that altered the ubiquitination landscape at the base of the amniote lineage with potential effects on amniote biology and evolution.